2021
DOI: 10.3390/v13122459
|View full text |Cite
|
Sign up to set email alerts
|

Encapsidation of Staufen-2 Enhances Infectivity of HIV-1

Abstract: Staufen, the RNA-binding family of proteins, affects various steps in the Human Immuno-Deficiency Virus (HIV-1) replication cycle. While our previous study established Staufen-2–HIV-1 Rev interaction and its role in augmenting nucleocytoplasmic export of RRE-containing viral RNA, viral incorporation of Staufen-2 and its effect on viral propagation were unknown. Here, we report that Staufen-2 interacts with HIV-1 Gag and is incorporated into virions and that encapsidated Staufen-2 boosted viral infectivity. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The nature of these interacting proteins could influence the fate of the viral life cycle. For instance, in our recent study, we demonstrated that Staufen‐2 is incorporated into virions that influence both viral production and infectivity [35]. These observations open new avenues of investigation and are also a part of the ongoing research in our lab.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The nature of these interacting proteins could influence the fate of the viral life cycle. For instance, in our recent study, we demonstrated that Staufen‐2 is incorporated into virions that influence both viral production and infectivity [35]. These observations open new avenues of investigation and are also a part of the ongoing research in our lab.…”
Section: Discussionmentioning
confidence: 84%
“…For the construction of Staufen‐2 knockout HEK293T cells, CRISPR‐Cas9 techniques were used as described earlier [35], and Western blotting was carried out to confirm the Staufen‐2 knockout marked by its absence as compared to wildtype vector control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmids expressing different domains of NUP98 cloned in pEGFPC1 and full-length Myc-NUP98 cloned in pcDNA were a kind gift from Dr. Maureen Powers (Emory University, Atlanta, USA) ( 53 ). pSIV AGM -Luc-R − E − Δvif was a kind gift from Carsten Munk (Heinrich-Heine-University, Düsseldorf, Germany) ( 54 ). pNLC4.3GFP was a kind gift from Prof. Barbara Muller (University of Heidelberg, Germany) ( 55 ).…”
Section: Methodsmentioning
confidence: 99%
“…The efficiency of the knockdown of NUP98 by shRNA was determined by Western blotting using anti-NUP98 antibody. The lentivirus used for the knockdown of NUP98 in SupT1 cells was prepared by transfecting HEK293T cells with packaging and transfer vectors as previously described ( 54 ). Briefly, HEK293T cells in a six-well plate were co-transfected with VSV-G encoding pMD2.G (250 ng), Gag-Pol encoding psPAX2 (1,000 ng), and pLKO.1-Puro (1,000 ng) harboring NUP98-specific shRNA sequences by the calcium phosphate method.…”
Section: Methodsmentioning
confidence: 99%